Revitalization of clinical skills training at the University of the Western Cape - J.D. Jeggels; A. Traut; M. Kwast (AOSIS, 2010)
Most educational institutions that offer health related qualifications make use of clinical skills laboratories. These spaces are generally used for the demonstration and assessment of clinical skills. The purpose of this paper is to share our experiences related to the revitalization of skills training by introducing the skills lab method at the School of Nursing (SoN), University of the Western Cape (UWC). To accommodate the contextual changes as a result of the restructuring of the higher education landscape in 2003, the clinical skills training programme at UWC had to be reviewed. With a dramatic increase in the student numbers and a reduction in hospital beds, the skills lab method provided students with an opportunity to develop clinical skills prior to their placement in real service settings. The design phase centred on adopting a skills training methodology that articulates with the case-based approach used by the SoN. Kolb's, experiential learning cycle provided the theoretical underpinning for the methodology. The planning phase was spent on the development of resources. Eight staff members were trained by our international higher education collaborators who also facilitated the training of clinical supervisors and simulated patients. The physical space had to be redesigned to accommodate audio visual and information technology to support the phases of the skills lab method. The implementation of the skills lab method was phased in from the first-year level. An interactive seminar held after the first year of implementation provided feedback from all the role players and was mostly positive. The results of introducing the skills lab method include: a move by students towards self-directed clinical skills development, clinical supervisors adopting the role of facilitators of learning and experiential clinical learning being based on, amongst others, the students' engagement with simulated patients. Finally, the recommendations relate to tailor-making clinical skills training by using various aspects of teaching and learning principles, i.e. case-based teaching, experiential learning and the skills lab method.